Adaptive budgeting in conditions of emergency situations and military uncertainty: the role of digital tools in public financial management - Kruhlov, Vitaliy; Tereshchenko, Dina (Pressing Problems of Public Administration, 2024)
The article “Adaptive Budgeting in the Context of Emergencies and Wartime Uncertainty: The Role of Digital Tools in Public Finance Management” addresses the theoretical and practical aspects of using digital technologies to enhance the flexibility and adaptability of the budgeting process in highly volatile conditions. The study emphasizes the unique challenges posed by prolonged wartime uncertainty in Ukraine and explores opportunities for post-war recovery through the integration of digital tools such as scenario modeling and machine learning. The research is structured into three key sections. The first part outlines the theoretical and methodological foundations of adaptive budgeting, defining its essence, principles, and critical role in emergencies. It examines the specific features of budgeting in crises and the importance of digital technologies in ensuring responsive and flexible resource allocation. The second section provides a comparative analysis of global best practices, focusing on the application of scenario modeling, machine learning, and open-budget systems. It identifies challenges and opportunities in implementing these tools under conditions of uncertainty. The third section proposes directions for improving adaptive budgeting in Ukraine, offering practical recommendations for integrating digital technologies into the public finance management system. The study is grounded in a systemic approach, viewing the budgeting process as a complex adaptive system that responds to external changes through feedback mechanisms and resource flexibility. Using methods of analysis, synthesis, comparative analysis, and scenario modeling, the research identifies the key factors affecting adaptability and substantiates ways to enhance it through digitalization. The informational base includes scientific literature, Ukrainian regulatory acts, and data from institutions such as the Ministry of Finance of Ukraine and international organizations like the IMF and OECD. Key findings highlight the transformative potential of digital tools in public finance management during crises. Global experience demonstrates that technologies such as cloud computing, predictive analytics, and blockchain significantly improve transparency, inclusivity, and efficiency in resource allocation. However, successful digital transformation requires more than technology; it depends on cultural shifts, the development of digital competencies, and robust collaboration between stakeholders. The article concludes with specific recommendations for Ukraine. These include leveraging predictive analytics to enhance financial planning, integrating blockchain to ensure transparency and trust in financial transactions, and expanding participatory budgeting practices. The study underscores the importance of systemic digital transformation in public finance to address the challenges of resource scarcity, economic volatility, and fiscal risks. Implementing adaptive budgeting, supported by advanced technologies, can become the cornerstone for Ukraine’s sustainable recovery and its alignment with European integration objectives. The practical implications of this research extend beyond crisis response, offering a foundation for long-term fiscal resilience. By integrating global best practices and adapting them to Ukraine’s unique context, adaptive budgeting can provide the agility and accountability needed to rebuild a nation on principles of transparency, inclusivity, and sustainable development.